THE PERSPECTIVE OF LIVING HADITH ON WOMEN’S LEADERSHIP IN FATAYAT OF NAHDATUL ULAMA - Irma Nur Hayati; Umi Sumbulah (Riwayah: Jurnal Studi Hadis, 2024)
Islam considers that women and men are the two foundations of society where they have the same role in creating, forming, regulating and utilizing society. Islam has also given various rights, honors and obligations to women in accordance with their honor and dignity as creatures who are responsible before Allah, both towards themselves, their families, society and the state. If Allah had given women the rights and responsibilities, namely to be “human” as servants of Allah, there would be no reason for men to feel superior to the female gender. Men and women are both creatures of Allah who will be held accountable in the afterlife for the rest of their lives. Women’s empowerment and gender issues are very interesting to discuss at the moment. This research discusses the Living Hadith perspective on women’s leadership in the Fatayat Nahdatul Ulama organization in Jobang District, Jember Regency in 2022. This non-formal institution operating in the religious, social and educational fields is phenomenal and has become a trend in society. One of the problems that arises among women’s empowerment activists is their form of involvement in the public sphere which causes controversy. The aim of this research is to explain: what, why and how the Living Hadist perspective on women’s leadership at the Nahdatul Ulama fatayat in Jombang sub-district - Jember district. This research will be studied in more depth by collecting information from various sources; books, internet, social media, and articles. Descriptive qualitative methods were used to analyze the collected data. The results of this research provide enlightenment that women’s leadership from the Living Hadith perspective can explain a new understanding that there is a Watasiyah Principle in the context of women’s Islamic organizational leadership.